2022
DOI: 10.1093/humupd/dmac034
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of psychological interventions for mental health and pregnancy rates among individuals with infertility: a systematic review and meta-analysis

Abstract: BACKGROUND Depression and anxiety are highly prevalent among individuals struggling with infertility. Thus, numerous psychological interventions have been adapted to infertility, with the aim of relieving distress as well as increasing pregnancy rates. OBJECTIVE AND RATIONALE This systematic review and meta-analysis aimed to identify all randomized controlled trials (RCTs) evaluating the effect of psychological interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 79 publications
0
16
0
1
Order By: Relevance
“…The systematic review and meta-analysis of Dube et al [ 23 ] (which has been published exactly at the time of completion of this review) showed that psychosocial interventions for women had a 25% higher probability of becoming pregnant than those who did not receive treatment. Art/music therapy, yoga, acupuncture and massage therapy were excluded as psychosocial interventions because they were not considered psychologically based.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The systematic review and meta-analysis of Dube et al [ 23 ] (which has been published exactly at the time of completion of this review) showed that psychosocial interventions for women had a 25% higher probability of becoming pregnant than those who did not receive treatment. Art/music therapy, yoga, acupuncture and massage therapy were excluded as psychosocial interventions because they were not considered psychologically based.…”
Section: Discussionmentioning
confidence: 98%
“…Katyal et al [ 24 ] found an improvement in pregnancy rates in their meta-analysis. This increased when only long-duration interventions were considered, which excluded music therapy interventions (comparable with [ 23 ], see below).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations